PENYELIDIKAN BIDANG GELINCIR MENGGUNAKAN METODA GEOLISTRIK TAHANAN JENIS KONFIGURASI SCHLUMBERGER DI DESA KAMPUNG MANGGIS KECAMATAN PADANG PANJANG BARAT - Lismalini Lismalini (PILLAR OF PHYSICS, 2014)
The investigation of slip surface in  Kampung Manggis  Padang Panjang Barat has been done. The aim of this research is to know the shape of slip surface in that area. This research use resistivity geoelectrical method with Schlumberger configuration. Data are colected in four track which is made paralel by ARES (Automatic Resistivity meter). Processing of data was done using Res2Dinv v3.57 software with standard constraint least squares inversion in order to make 2D model of earth’s surface. The result of this research  shows that slip sufrace is Translational Slip that is almost  parallel with land surface. The resistivity values of first’s slip surface around 142.00-273.00 Ωm in 10.30 m deepness and the second one around 121.00–225.00 Ωm in 10.80 m deepness. The rock in slip surface is interpreted as Limestone. Keywords - Slip Surface, resistivity geoelectrical method, Schlumberger